2021
DOI: 10.1101/2021.01.26.21250482
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fallow time determination in dentistry using aerosol measurement

Abstract: AimTo calculate fallow time (FT) required following dental aerosol generating procedures (AGPs) in both a dental hospital (mechanically ventilated) and primary care (non-mechanically ventilated). Secondary outcomes were to identify spread and persistence of aerosol in open clinics compared to closed surgeries (mechanically ventilated environment), and identify if extra-oral scavenging (EOS) reduces production of aerosol and FT.MethodsIn vitro simulation of fast handpiece (FHP) cavity preparations using a manik… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…We determined a wide variation in the time for particles of all sizes to return to pre-AGP levels, although larger particles required less time with the HSCAH. Shahdad et al (2021) reported similar variability and suggested that fallow time estimates were longer for procedures where the handpiece was used in 5-min bursts, comparable to our protocol. A recent study indicated that <0.1% of aerosolized fluorescein dye was detectable after 30 min of fallow time ( Allison et al 2021 ).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…We determined a wide variation in the time for particles of all sizes to return to pre-AGP levels, although larger particles required less time with the HSCAH. Shahdad et al (2021) reported similar variability and suggested that fallow time estimates were longer for procedures where the handpiece was used in 5-min bursts, comparable to our protocol. A recent study indicated that <0.1% of aerosolized fluorescein dye was detectable after 30 min of fallow time ( Allison et al 2021 ).…”
Section: Discussionsupporting
confidence: 77%
“…It uses artificial teeth, which lack the anatomical intricacies of human teeth. However, previous particle analyses revealed little difference between plastic and real teeth ( Shahdad et al 2021 ). Our model does not imitate the effects of a patient breathing or other patient behaviors, such as talking or coughing, that would likely contribute to bioaerosol production.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations